2013
DOI: 10.1097/nxn.0b013e3182771880
|View full text |Cite
|
Sign up to set email alerts
|

Judging Nursing Information on the World Wide Web

Abstract: The World Wide Web is increasingly becoming an important source of information for healthcare professionals. However, finding reliable information from unauthoritative Web sites to inform healthcare can pose a challenge to nurses. A study, using grounded theory, was undertaken in two phases to understand how qualified nurses judge the quality of Web nursing information. Data were collected using semistructured interviews and focus groups. An explanatory framework that emerged from the data showed that the judg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Most of the respondents in this study reported checking the quality of online material by currency and author criteria, along with a range of strategies similar to those reported in a research study of how nurses judge the quality of nursing information on the web . Wikipedia was identified as a key source of online information for some respondents in this study and the associated medical ward study which has also been found in studies of physicians and pharmacists .…”
Section: Discussionmentioning
confidence: 58%
“…Most of the respondents in this study reported checking the quality of online material by currency and author criteria, along with a range of strategies similar to those reported in a research study of how nurses judge the quality of nursing information on the web . Wikipedia was identified as a key source of online information for some respondents in this study and the associated medical ward study which has also been found in studies of physicians and pharmacists .…”
Section: Discussionmentioning
confidence: 58%
“…Studies showed that with increasing information resources on the internet, students are rarely using the university library to retrieve information, and their use of the Web as a source of information has increased remarkably (Metzger et al, 2003). Research also shows that people rely heavily on the internet to retrieve information, and university students are an avid user group of this technology (Flanagin and Metzger, 2001, 2011, 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Chu et al, 2018; Gao et al, 2015; Khosrowjerdi, 2019; Mansour, 2018; Shen et al, 2019; Sohn and Choi, 2019), applied qualitative methods (e.g. Cader, 2013; Madden et al, 2012; O’Reilly and Marx, 2011) or mixed methods (e.g. Zhang and Yuan, 2019).…”
Section: Research Backgroundmentioning
confidence: 99%
“…They declared that the quality of health information answers on question and answer sites is doubtful. The results of the study by Cader (2013) about evaluating the quality of web nursing information demonstrated that the judgment process relies on the types of knowing and modes of cognition, especially the level of web information cues, the nurses’ basic skills, and the available time. In the study of Chung et al (2010), trustworthiness, expertise, and attractiveness were considered and measured as the main constructs of information credibility in online newspapers.…”
Section: Research Backgroundmentioning
confidence: 99%